Dinâmica espacial da cadeia de lácteos no Sudoeste paranaense: políticas públicas, inovação e estratégias empresariais. - Vieira, Francieli Borges (2019)
The present work deals about the spatial dynamics of the dairy chain, emphasizing its characteristic in the Southwest region in Parana, between 2000-2018. It aims to identify the main business strategies as well the factors that explain the capital´s dynamics especially in the Southwest of Parana. When analyzing the development of the milk production chain, sought to establish an interconnection between economic, social and geographic factors. The proposed theoretical referential, the historical materialism, gives support for the analysis of empirical data, obtained through entrepreneurs’ interviews and other agents in the dairy sector, in addition to the analysis of statistical data from public agencies such as EMATER, IBGE, EMBRAPA etc. The set of transformations that occurred in the milk production chain was made possible by several segments, among them the central role played by the industrial sector stands out. With the intensification of competition, there was a need to make important strategic and productive changes. The industrial restructuring process culminated in the diversification of production and the concentration of capital, through mergers and acquisitions, intensifying the participation of foreign companies in the national market. The business strategies adopted were the differentiation in products and increasing the scale of production, providing the expansion of the geographic scale acting in the companies. Public policies were essential for the process of modernizing dairy production, because it enabled companies acting both with regard to industrial transformation as in transport and primary production. The Southwest of Parana, the region whose socio-spatial formation was based on small merchant production, became one of the main dairy basins in the southern region of Brazil, largely based on knowledge of dairy production since the beginning of its colonization and the public policies that provided agricultural modernization, enabling it to act as a national dairy basin.